COMBINATION OF CAT STRETCH EXERCISE MOVEMENTS WITH COUNTER PRESSURE TECHNIQUE ON MENSTRUAL PAIN - Meuthia Deva Amalia; Desmawati Desmawati; Lina Ayu Marcelina; Dora Samaria (Poltekkes Kemenkes Jakarta III, 2026)
Menstrual pain, or dysmenorrhea, is primarily associated with increased production of prostaglandins, which trigger uterine contractions and result in pain during menstruation. This condition affects approximately 29% of women, with around 12% frequently missing school each month. This study aimed to evaluate the effectiveness of combining cat stretch exercises (CSE) with counter pressure (CP) techniques in reducing menstrual pain among seventh-grade students. A quasi-experimental design with a pre-test and post-test control group approach was employed. A total of 56 respondents were selected through purposive sampling and divided into intervention and control groups. Pain intensity was measured using the Numeric Rating Scale (NRS), and the intervention was implemented according to standard operating procedures (SOP). Data were analyzed using Paired Sample t-test and Independent t-test to assess within-group and between-group differences. The results showed that the mean pre-test pain score was 4.36 ± 1.471 in the intervention group and 4.71 ± 2.034 in the control group, with no statistically significant difference (p = 0.455). After the intervention, the mean pain score decreased to 2.14 ± 1.407 in the intervention group and 3.21 ± 1.931 in the control group, indicating a statistically significant difference between groups (p = 0.021). In conclusion, there was a statistically significant reduction in menstrual pain among students who received the combination of cat stretch exercises and counter pressure techniques. These findings suggest that this combined intervention may be considered as a complementary approach to help manage menstrual pain in school settings, although further research with more rigorous designs is recommended.